Characterisation and refinement of properties of glass fibre reinforced polyester polymer concrete for use in manhole components - Griffiths, Robert (Centre for Materials Engineering, 2016)
The aim of this investigation is to characterise and refine the physical properties of glass fibre reinforced polyester polymer concrete. This material is currently being employed by AV Mouldings (Pty) Ltd. to manufacture manhole and drain components according to specifications existing for cast iron covers. No specification exists for polymer concrete. In particular it has been found that there is a large market for Type 2A replacement manhole covers and frames due to the current problem in South Africa of the cast iron versions being stolen and sold for scrap metal. It has been found that polymer concrete covers manufactured to replace stolen cast iron covers (in existing cast iron frames) fail occasionally in service. The investigation thus focuses on the characterisation of glass fibre reinforced polymer concrete and analysis of the current standards with a view to establishing a new South African Bureau of Standards (SABS) specification for polymer concrete manhole components. The main testing procedure involved flexural testing of beam specimens. Preliminary tests were carried out to measure strength, toughness, strain rate sensitivity, and the effect of different reinforcing materials. Accelerated degradation tests were then conducted to establish the materials resistance to UV radiation, acids, alkalis, and various solvents. Different resins were evaluated, and experiments were conducted using graded aggregates, in an attempt to reduce the number of voids in the material. Vibratory moulding techniques and postcuring methods were also evaluated. The viability of employing silane coupling agents in polymer concrete was investigated in detail towards the end of the research. Redesign of the Type 2A replacement cover was then undertaken.